US-China Conflict : Will ASEAN Centrality Be Derailed? - Yang Razali Kassim (2019)
The US-China trade war is fast escalating into a political one with security implications as US senators re-introduced a sanctions bill to check Beijing on its expansionism in the South China Sea and East China Sea. How will ASEAN be impacted?